Upaya Guru Dalam Mengatasi Kesulitan Belajar Membaca Permulaan Siswa Kelas II MI Ma’arif Pejagoan Kebumen - Rizki Ariyanto; Imam Subarkah; Nadia Raifah Nawa Kartika (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to analyze the teacher's efforts to overcome students' initial reading difficulties.The approach used is descriptive qualitative. The subjects were three students and one teacher andthe location chosen for research was MI Ma'arif Pejagoan. Data collection techniques includeobservation, interviews and documentation. The data analysis technique is through data reductionactivities, data presentation and verification or drawing conclusions. Based on the results of theresearch, the efforts made by teachers to students who have difficulty reading the beginning are bygiving additional hours to students when they come home from school, through the use of thesyllable method and in collaboration with the guardians of students to participate in motivatingtheir children to be diligent in reading